INTERCULTURAL VALUES IN THE DIGITAL CULTURE OF YOUTH: PROMOTION FROM EDUCATION - Elena Zhizhko (Вісник Кафедри ЮНЕСКО «Неперервна професійна освіта ХХІ століття», 2025)
This article presents the results of a pedagogical study aimed at exploring the theoretical foundations for developing educational strategies that direct the abilities and skills of young people – shaped by digital culture and social networks – towards intercultural dialogue. The author critically analyses how digital communication technologies, while offering vast opportunities for education, professional development, and intercultural connectivity, simultaneously exacerbate social pathologies such as intolerance, irresponsibility, misogyny, and emotional instability. These phenomena disproportionately affect young users, who often oscillate between being victims and agents of harm in digital environments. Drawing on the principles of transhumanism, bioethics, the theory of communicative action (Habermas), and the pedagogy of otherness (Ortega), the article argues for a paradigm of education that is ethically grounded and emotionally responsive. It positions educators as key mediators in helping digital natives cultivate intercultural values, navigate the complexities of online interactions, and engage in respectful and reflective communication. The study employs a qualitative, document-based methodology, incorporating interdisciplinary scholarship from Ibero-American, European, and global contexts. The author highlights the pedagogical potential of fostering emotional literacy, digital ethics, and dialogic communication as central elements in shaping a globally competent, socially responsible youth. Case studies and contemporary literature (e.g., Cleofas, Zhang, Vojtáš) demonstrate the relevance of educational interventions that integrate digital citizenship with intercultural education. Ultimately, the study concludes that education in digital society must not be reduced to technical knowledge or information transmission, but should aim at the holistic development of learners – empowering them to live with, for, and through the Other in both physical and virtual realms.